The increase of crystal growing rate without damaging the smoothness of interface border - Kanishchev, V.N. (Functional Materials, 2013)
This paper provides literature data on non-stationary crystallization of binary melt, making it possible to put forward a hypothesis about a fluctuation mechanism of the structure transitions on the interface surface. Another argument for this hypothesis is the authors' observation results of the front crystallization at growing a sapphire crystal by horizontal directed crystallization. It has been suggested that it will be possible to grow crystals with a smooth interface border faster at a variable rate of crystallization rather than at a constant one.